Penjualan Obat Antidiabetes Kombinasi (Jardiance Duo®) Pada Platform E-Commerce Tokopedia - Nata, Ririsiana; Soegiantoro, Didiek Hardiyanto; Kurniawati, Aloysia Yossy; Kristiyani, Ani (Innovative: Journal Of Social Science Research, 2025)
Type 2 diabetes mellitus (T2DM) is a major health problem in Indonesia with increasing prevalence, driven by lifestyle changes and urbanization. The combination of Metformin and Empagliflozin in the Jardiance Duo® product is one of the effective therapies of choice in managing T2DM. Along with the development of e-commerce in the pharmaceutical sector, the Tokopedia platform has begun to provide access to purchase this drug online. This study aims to analyze the effect of selling price and seller's domicile on the sales volume of Jardiance Duo® on Tokopedia. The problems studied include the extent to which selling price influences purchasing decisions and how the geographic distribution of sellers contributes to sales levels. The study used a quantitative-descriptive approach, with data collected through direct observation on the Tokopedia platform on May 23, 2025. The data studied included price, seller location, and sales volume for each Jardiance Duo® variant. The results showed that the selling price in the range of IDR 443,000–IDR 485,000 had the highest sales volume, reflecting high price sensitivity among consumers. The 12.5/500 mg variant was the best-selling, with the highest sales recorded in West Java and East Java. D.I. Yogyakarta recorded no sales at all, indicating an imbalance in geographical distribution. In addition, the uneven pricing between sellers creates uncertainty for consumers regarding the authenticity of the product. The conclusion of this study emphasizes the importance of a competitive pricing strategy and equitable distribution between regions, as well as the need for price regulation and consumer education to increase trust in online drug purchases. These results are expected to be the basis for consideration for digital pharmaceutical industry players and e-commerce platforms in developing more effective distribution and marketing strategies.